Inhibition of bacterial growth on marble stone of 18th century by treatment of nanoencapsulated essential oils. (March 2020) - Romano, Ida; Granata, Giuseppe; Poli, Annarita; Finore, Ilaria; Napoli, Edoardo; Geraci, Corrada
Abstract: Controlling of cultural heritage biodeterioration is a serious problem in the world. Chemical biocides, used to kill unwanted microorganism, can represent a risk for human health and environment, and interfere with the restoration material. Natural biocides could represent a valid alternative to conventional ones. In this study we report the use of nanocapsules suspensions (NCs) loaded with Origanum vulgare and Thymus capitatus essential oils (EOs) to contrast the development of bacterial growth of two microrganisms (Escherichia coli and Kokuria rhizophila) on the marble stone from 18th century church altar. No structural change was observed on the stone after treatment with the aqueous suspension containing nanoparticles as evidenced by SEM-EDX analysis. The nanostructurate systems (EO-NCs) were able to inhibit the bacterial grow on the stone pretreated with bacterial inoculum as showed by agar discs contact test. Nanocapsules, based on biodegradable and biocompatible polymer (poly(ε-caprolactone)), loaded with thyme EO are more efficient than nanocapsules loaded with oregano EO. The obtained results evidenced the potential of these natural biocides in the treatment of biodeteriorated cultural heritage. Graphical abstract: Image 1 Highlights: Natural biocides a valid alternative to conventional ones. Nanocapsules loaded with essential oils inhibit the growth of Gram+ and Gram-bacterial strains. Nanocapsules loaded with thyme essential oil are more active. 18th century marble stone as model material to test antimicrobial activity of essential oil nanocapsules.